Geothermal steam pretreatment of coconut coir dust using the modified rapid steam hydrolysis (M-RASH) - Nwoke, Felix I. (1993, 1993)
A pretreatment process for treatment of biomass waste materials, known as Modified Rapid System Hydrolysis (M-RASH), was designed and fabricated. Experiments were conducted at Mak-Ban geothermal power plant in Bay, Laguna. The M-RASH process was found to be an efficient pretreatment method for biomass waste materials fractionation and separation of the three major constituents: cellulose, hemicellulose and Lignin with minimum degradation of sugar content. Coconut coir dust (waste product of Coconucifera Linn) waste materials were reduced to different mesh sizes, ranging from mesh 20 to mesh 100. Cellulose content of 57.83% was observed in mesh 20 from geothermal steam pretreated samples at 155°C, and 57.40 percent from generated boiler stream pretreated samples at 200°C and one minute reaction time. The lignin content dropped quickly at temperatures above 155°C, as observed in mesh 20, from generated boiler steam pretreated samples with lignin content of 16.02 percent at 200°C. The hemicellulose's content ranges from 4.96 to 6.68 percent for all mesh sizes. At a longer pretreatment reaction time of 5 minutes, the cellulose content was 82.80 percent for mesh 20 geothermally pretreated samples, and 95 percent reduction of the lignin content observed ranges from 1.35 to 2.88 percent for all mesh sizes. However, degradation of hemicellulose content was observed at longer pretreatment reaction time (above 5 minutes) and mesh 20 had the greatest loss of polymer fragments. The cellulose conversion to glucose of prehydrolysis samples of mesh 20 had the highest glucose yield of 53.19 percent at 155°C temperature and one minute raction time. The acid hydrolysis of geothermally pretreated samples for mesh 20 gave a glucose yield of 75.45 percent, based on the original available glucose of untreated samp
A mathematical model that was formulated based on the Volume reaction model (homogenous model) predicted a cellulose fractional conversion of 59.88 percent at 155°C, and lignin fractional conversion of 33.4 percent at 200°C, corresponding to lignin content of 8.72 percent. The model used the effectiveness factor, thiele modulus and performance factor to account for the rate occurring in a solid (coir dust) - gas/fluid (geothermal steam) non-catalytic reacti9on. The effectiveness factor (EF) of lignin and hemicellulose components gave rise to effectiveness values greater than unity, while the cellulose component did not exceed the effectiveness value of unity at higher isothermal temperature runs. The critical Thiele modulus (Qcrit) predicted by the model was 1.25 and at Thiele Modulus of 0 =>5.0m a shorter reaction time is required to delignify the coir dust waste materials. The assumption of zeroth order (m=o) with respect to geothermal steam and first order (n=1) with respect to coir dust was considered as a valid assumption, based on the performance parameter. The numerical algorithm of the orthogonal collocation method overestimated the cellulose values at high temperatures, while the Runge Kutta - Simpson's technique gave values that were veryclose to the experimental results. However, the predicted values of lignin from both numerical methods were good and close to the experimental results. The activation energy of the cellulose and hemicellulose components were a bit low compared to the activation energy reported by other investigators on some biomass waste materials. A statistics analysis gave a good correlation of R-square equal to or greater than 90 (R^2=> 90) for all constituents of coir
Computer print-out (photocopy).
Thesis (Ph.D. Energy Engineering)--University of the Philippines Diliman.
Keywords: Coir; Biomass conversion; Biomass energy -- Philippines; Hydrolysis; Waste products as fuel -- Philippines